2019
DOI: 10.1017/ice.2019.251
|View full text |Cite
|
Sign up to set email alerts
|

Nursing preference for alcohol-based hand rub volume

Abstract: Background:The effectiveness of alcohol-based hand rub (ABHR) is correlated with drying time, which depends on the volume applied. Evidence suggests that there is considerable variation in the amount of ABHR used by healthcare providers.Objective:We sought to identify the volume of ABHR preferred for use by nurses.Methods:A prospective observation study was performed in 8 units at a tertiary-care hospital. Nurses were provided pocket-sized ABHR bottles with caps to record each bottle opening. Nurses were instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…One possible solution to increase volume and application time in clinical practice is to standardise dispensers to ensure the required ABHR volume is delivered by a single dispenser action. A recent observational study of the ABHR volumes showed that the average ABHR volume used was only 1.09 ml (SD: 0.61), a dose similar to that delivered by the hospital’s automated ABHR dispensers (1.1ml) [ 46 ]. Yet, a recent study [ 47 ] investigating the dispensing performance of 22 wall-mounted ABHR dispensers commonly used in hospitals showed that the ABHR volume delivered by the dispensers was influenced by the ABHR format, the level of ABHR present in the container and the time lapse between dispenser uses.…”
Section: Discussionmentioning
confidence: 99%
“…One possible solution to increase volume and application time in clinical practice is to standardise dispensers to ensure the required ABHR volume is delivered by a single dispenser action. A recent observational study of the ABHR volumes showed that the average ABHR volume used was only 1.09 ml (SD: 0.61), a dose similar to that delivered by the hospital’s automated ABHR dispensers (1.1ml) [ 46 ]. Yet, a recent study [ 47 ] investigating the dispensing performance of 22 wall-mounted ABHR dispensers commonly used in hospitals showed that the ABHR volume delivered by the dispensers was influenced by the ABHR format, the level of ABHR present in the container and the time lapse between dispenser uses.…”
Section: Discussionmentioning
confidence: 99%
“…Even Hydrogen Peroxide at 0.5% concentration has been reported to decrease the infection capability of human coronaviruses, when used for a minute [14] 2.6.Volume Some studies have reported that in a hospital setting, the volume of ABHR dispensed by the hospital's automated dispenser is close to 1.1 mL per dose and the ABHR dose is inversely related with the number of applications of ABHR per shift, but has no relationship with the hand size, although there is a concern that it might create a risk for people with larger hand size. [15]…”
Section: 5formulationmentioning
confidence: 99%